Associations between metabolites and pancreatic cancer risk in a large prospective epidemiologic study - Stolzenberg-Solomon, Rachael Z. (Gut, 2020)
OBJECTIVE: To assess whether pre-diagnostic metabolites were associated with incident pancreatic ductal adenocarcinoma (PDAC) in a prospective cohort study. DESIGN: We conducted an untargeted analysis of 554 known metabolites measured in pre-diagnostic serum (up to 24 years) to determine their association with incident PDAC in a nested-case control study of male smokers (372 matched case-control sets) and an independent nested case-control study in that included women and non-smokers (107 matched sets). Metabolites were measured using Orbitrap Elite or Q-Exactive high resolution/accurate mass spectrometers. Controls were matched to cases by age, sex, race, date of blood draw and follow-up time. We used conditional logistic regression adjusted for age to calculate odds ratios (OR) and 95% confidence intervals (CI) for a 1 standard deviation increase in log-metabolite level separately each cohort and combined the two ORs using a fixed effects meta-analysis. RESULTS: Thirty-one metabolites were significantly associated with PDAC at an FDR < 0.05 with 12 metabolites below the Bonferroni-corrected threshold (P-value < 9.04 × 10(−5)). Similar associations were observed in both cohorts. The dipeptides glycylvaline, aspartylphenylalanine, pyroglutamylglycine, phenylalanylphenylalanine, phenylalanylleucine, and tryptophylglutamate and amino acids aspartate and glutamate were positively while the dipeptides tyrosylglutamine and α-glutamyltyrosine, fibrinogen cleavage peptide DSGEGDFXAEGGGVR, and glutathione related amino acid cysteine-glutathione disulfide were inversely associated with PDAC after Bonferroni correction. Five top metabolites demonstrated significant time varying associations (P-value < 0.023) with the strongest associations observed 10–15 years after participants’ blood collection and attenuated thereafter. CONCLUSION: Our results suggest that pre-diagnostic metabolites related to subclinical disease, γ-glutamyl cycle metabolism, and adiposity/insulin resistance are associated with PDAC.